Pengaruh Tingkat Pendidikan Ibu Hamil Terhadap Kemampuan Mengenali Tanda Bahaya Kehamilan - Rachmawati Ika Sukarsih (Jurnal Keperawatan Muhammadiyah, 2022)
The maternal mortality rate in Indonesia in 2018 was the highest of any country at 214 per 100,000 live births. One of the goals in the SDGs sector is to reduce the maternal mortality rate to 70 per 100,000 live births. In 2016 the MMR in the city of Surabaya was at 85.72/100,000 live births or equivalent to 37 people. Then in 2017 with an MMR of 79.40 per 100,000 live births or a total of 34 maternal deaths. Various efforts have been made to reduce MMR through the Safe Motherhood Initiative program, P4K, GSI, Sijari Emas in 2000. This research is a quantitative study with a correlational approach with the aim of knowing the effect of the education level of pregnant women on the ability to recognize danger signs of pregnancy. Of the 35 people who were used as research samples, significant results were obtained about the effect of the education level of pregnant women on the ability to recognize the danger signs of pregnancy. Knowledge of pregnant women greatly affects the ability of pregnant women to recognize danger signs of pregnancy and types of danger signs in pregnancy. The level of education is one of the trigger factors that play a role in influencing a person's decision to behave in a healthy life. Conclusion: The level of education of pregnant women greatly affects the ability to recognize the danger signs of pregnancy.